BAFF and BAFF-Receptor in B Cell Selection and Survival - Smulski, Cristian R.; Eibel, Hermann (Frontiers in Immunology, 2018)
The BAFF-receptor (BAFFR) is encoded by the TNFRSF13 gene and is one of the main pro-survival receptors of B cells. Its function is impressively documented by a homozygous deletion within the TNFRSF13C gene, which leads to an almost complete block of B cell development at the stage of immature/transitional B cells. The resulting immunodeficiency is characterized by B-lymphopenia, agammaglobulinemia and impaired humoral immune responses. However, different from mutations affecting pathway components coupled to B cell antigen receptor (BCR) signaling, BAFFR-deficient B cells can still develop into IgA-secreting plasma cells. Therefore, BAFFR deficiency in humans is characterized by very few circulating B cells, very low IgM and IgG serum concentrations but normal or high IgA levels.